Uber: A New Challenge for Regulation and Competition Law? - Margherita Colangelo; Mariateresa Maggiolino (Market and Competition Law Review, 2017)
The rise of new software platforms presents regulators and antitrust agencies all over the world with a challenge. Should regulations adapt to the new services of the digital economy? Should competition law change its paradigm in relation to the sharing economy? Despite the growing expansion of these services, in most countries there is still no regulatory framework addressing these problems. Uber is the most emblematic example of this phenomenon. Indeed, it is subject to a large number of ongoing lawsuits merging many issues, ranging from questions pertaining to labour law of problems connected with unfair competition laws. This article first analyses the particular business model adopted by Uber and the antitrust concerns that it could raise. In so doing, the article pays heed to the approach that antitrust authorities should take towards the complex rivalry between (regulates) incumbents and (unregulated) new entrants. The article then considers the legal nature of the services provided by Uber, i.e. whether should be considered as transport services or as services of the information society. Either way, the chosen characterisation will affect the law applied to all digital platforms. The analysis, which adopts a comparative approach, focuses on the European context where national courts are in great turnmoil and the CJEU will be issuing a preliminary ruling on the nature of Uber services.